Antibiotic Resistance Profiles of Salmonella Recovered From Finishing Pigs and Slaughter Facilities in Henan, China - Jiang, Zenghai; Paudyal, Narayan; Xu, Yaohui; Deng, Tongwei; Li, Fang; Pan, Hang; Peng, Xianqi; He, Qigai; Yue, Min (Frontiers in Microbiology, 2019)
With the increase in commercial pig farming, there is a simultaneous increase in the use of antibiotics for prophylaxis as well as therapeutics in China. In this study, we evaluated the prevalence and resistance diversity of Salmonella isolated from faeces of asymptomatic, live and slaughtered pigs. We analyzed 1,732 pig faecal samples collected over eight months, at Henan province of China. Salmonella were isolated and identified by PCR. They were serotyped using commercial antisera and assayed for the MIC of 16 antibiotics by broth microdilution method. The average prevalence of Salmonella was 19.4% (95% CI: 17.6-21.4). Large farms (herd size ≥1,000) were found to have a higher prevalence as compared to the small and medium scale farms (P<0.0001). The prevalence of Salmonella in samples collected from the farms [11.77% (95% CI: 10.1-13.6)] and from the slaughterhouse [45.23% (95% CI: 40.3-50.30)] was statistically different (P<0.0001). The uncommon serovars of Salmonella such as Agama and common serovars such as Derby and Typhimurium were characterized. High resistance (>80%) was recorded towards ciprofloxacin (100%), tetracycline (99.4%), doxycycline (97%), sulfamethoxazole (85.8%), ampicillin (81.6%) and amoxicillin (80.4%). Multidrug resistance to four, five and seven classes of antibiotics was recorded to be approximately 25% in the most prevalent serovar like Derby. We conclude that the presence of alarmingly high resistance, towards the critical antibiotics such as quinolones and beta-lactams, in large swine farms in China, should draw public attention. These results highlight the need for enhancing antibiotic stewardship programs for judicious use of critical antibiotics in animal health as well as for producing safe pork.